Masses, Star Formation Efficiencies, and Dynamical Evolution of 18,000 H ii Regions - Pathak, Debosmita; Leroy, Adam K.; Barnes, Ashley. T.; Thompson, Todd A.; Lopez, Laura A.; Sandstrom, Karin M.; Sun, Jiayi; Glover, Simon C. O.; Klessen, Ralf S.; Koch, Eric W.; Larson, Kirsten L.; Lee, Janice; et al. (Institute of Physics Publishing, 2026)
We present measurements of the masses associated with ∼18,​​​​​000 H ii regions across 19 nearby star-forming galaxies by combining data from JWST, Hubble Space Telescope, MUSE, Atacama Large Millimeter/submillimeter Array, Very Large Array, and MeerKAT from the multiwavelength PHANGS survey. We report 10 pc-scale measurements of the mass of young stars, ionized gas, and older disk stars coincident with each H ii region, as well as the initial and current mass of molecular gas, atomic gas, and swept-up shell material, estimated from lower-resolution data. We find that the mass of older stars dominates over young stars at ≳10 pc scales, and ionized gas exceeds the stellar mass in most optically bright H ii regions. Combining our mass measurements for a statistically large sample of H ii regions, we derive 10 pc-scale star formation efficiencies of ≈6%–17% for individual H ii regions. Comparing each region’s self-gravity with the ambient interstellar medium (ISM) pressure and total pressure from presupernova stellar feedback, we show that most optically bright H ii regions are overpressured relative to their own self-gravity and the ambient ISM pressure and that they are hence likely expanding into their surroundings. Larger H ii regions in galaxy centers approach dynamical equilibrium. The self-gravity of regions is expected to dominate over presupernova stellar feedback pressure at ≳130 and 60 pc scales in galaxy disks and centers, respectively, but is always subdominant to the ambient ISM pressure on H ii region scales. Our measurements have direct implications for the dynamical evolution of star-forming regions and the efficiency of stellar feedback in ionizing and clearing cold gas.